2015
DOI: 10.5301/jva.5000423
|View full text |Cite
|
Sign up to set email alerts
|

Reduction or Discontinuation of Antibiotic Prophylaxis in Vascular Access Surgery, Tendon Sheath Incision and PD Catheter Placement

Abstract: Even in dialysis patients, neither pre- nor postoperative antibiotics are necessary for AVF and tendon sheath incision surgeries. AVG and PD catheter placement surgeries require only a small amount of antibiotics preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…One article by Nagai et al (7) was found eligible for this systematic review. This retrospective cohort study evaluated the role of prophylactic antibiotics to the incidence of surgical site infection (SSI) in n=651 patients post autogenous AVF, AVG and PD catheter placement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One article by Nagai et al (7) was found eligible for this systematic review. This retrospective cohort study evaluated the role of prophylactic antibiotics to the incidence of surgical site infection (SSI) in n=651 patients post autogenous AVF, AVG and PD catheter placement.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Nagai et al (7) could be subject to a degree of performance bias, as no information regarding the type of autogenous AVF, preparatory skin solution, duration of surgery and length of hospital stay was provided to the readers. However, given all patients were from a single institution, a logical assumption can be formulated that exposure of all individuals undergoing autogenous AVF in both groups of prophylactic and non-prophylactic group (n=136 vs n=475) were similar and/ or spread in terms of aforementioned factors.…”
Section: Discussionmentioning
confidence: 99%